2018
DOI: 10.1016/j.scitotenv.2018.04.150
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for the management of MSW incineration ashes from gas cleaning: New perspectives on recovery of secondary raw materials and circular economy

Abstract: Environmental policies in the European Union focus on the prevention of hazardous waste and aim to mitigate its impact on human health and ecosystems. However, progress is promoting a shift in perspective from environmental impacts to resource recovery. Municipal solid waste incineration (MSWI) has been increasing in developed countries, thus the amount of air pollution control residues (APCr) and fly ashes (FA) have followed the same upward trend. APCr from MSWI is classified as hazardous waste in the List of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
104
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 259 publications
(105 citation statements)
references
References 126 publications
0
104
0
1
Order By: Relevance
“…Several technologies, such as cement based techniques, chemical stabilization treatments, washing [8] and thermal techniques have been proposed to treat FA [9]. In particular, in recent years, the idea to develop sustainable technologies for waste remediation, in the frame of Azure chemistry approach [10], has contributed to promote the use of by-products and waste materials, as stabilizing agents, instead of use natural resources [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies, such as cement based techniques, chemical stabilization treatments, washing [8] and thermal techniques have been proposed to treat FA [9]. In particular, in recent years, the idea to develop sustainable technologies for waste remediation, in the frame of Azure chemistry approach [10], has contributed to promote the use of by-products and waste materials, as stabilizing agents, instead of use natural resources [11].…”
Section: Introductionmentioning
confidence: 99%
“…The method relies on the application of an electric current to the waste material and the subsequent removal of heavy metal ions in the electric field [5]. Untreated and treated MSWI fly ashes have been tested in building materials in laboratory stage [7][8][9][10]. In [11] untreated Greenlandic MSWI fly and bottom ash were added in mortars as cement replacement, and it was concluded that up to 5% of ashes could be stabilized successfully in the mortar.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is quantitatively evaluated that the use of eco-friendly materials in place of existing construction materials significantly reduces carbon footprint and energy consumption [8,9]. A safe and rational utilization of industrial solid waste, such as fly ash, is an increasingly important environmental concern because its cumulative landfill deteriorates water and soil contamination [10]. In particular, carbonation reaction of such waste has been reported to promote heavy metal stabilization, as well as uptake of atmospheric CO 2 [11].…”
Section: Introductionmentioning
confidence: 99%